High‐Throughput Differentiation and Screening of a Library of Mutant Stem Cell Clones Defines New Host‐Based Genes Involved in Rabies Virus Infection. (12th May 2015) - Wallis, Deeann; Loesch, Kimberly; Galaviz, Stacy; Sun, Qingan; DeJesus, Michael; Ioerger, Thomas; Sacchettini, James C.
Abstract We used a genomic library of mutant murine embryonic stem cells (ESCs) and report the methodology required to simultaneously culture, differentiate, and screen more than 3, 200 heterozygous mutant clones to identify host‐based genes involved in both sensitivity and resistance to rabies virus infection. Established neuronal differentiation protocols were miniaturized such that many clones could be handled simultaneously, and molecular markers were used to show that the resultant cultures were pan‐neuronal. Next, we used a green fluorescent protein (GFP) labeled rabies virus to develop, validate, and implement one of the first host‐based, high‐content, high‐throughput screens for rabies virus. Undifferentiated cell and neuron cultures were infected with GFP‐rabies and live imaging was used to evaluate GFP intensity at time points corresponding to initial infection/uptake and early and late replication. Furthermore, supernatants were used to evaluate viral shedding potential. After repeated testing, 63 genes involved in either sensitivity or resistance to rabies infection were identified. To further explore hits, we used a completely independent system (siRNA) to show that reduction in target gene expression leads to the observed phenotype. We validated the immune modulatory gene Unc13d and the dynein adapter gene Bbs4 by treating wild‐type ESCs and primary neurons with siRNA; treated cultures were resistant to rabies infection/replication. Overall, the potential of such in vitro functional genomics screens in stem cells adds additional value to other libraries of stem cells. This technique is applicable to any bacterial or virus interactome and any cell or tissue types that can be differentiated from ESCs. Stem Cells2015;33:2509–2522